2005
DOI: 10.1111/j.1468-005x.2005.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid workspace: re-spatialisations of work, organisation and management

Abstract: New information and communication technologies enable the spatial reconfiguration of work opening up possibilities for work to take place across multiple locations. This paper explores the implications of hybrid workspace through a new empirical study. It argues that spatial hybridity changes the nature of work, organisation and management across domestic space, organisational space and in cyberspace. IntroductionOne of the central issues in the study of new technology, work and employment has been the way tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
239
3
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(290 citation statements)
references
References 25 publications
10
239
3
11
Order By: Relevance
“…They point at potential downsides of NWW: loss of social support from colleagues when working from home (Halford, 2005), increased stress due to high responsibility, constant connectivity to work and loss of structure (e.g. Allvin et al, 2011;Mazmanian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They point at potential downsides of NWW: loss of social support from colleagues when working from home (Halford, 2005), increased stress due to high responsibility, constant connectivity to work and loss of structure (e.g. Allvin et al, 2011;Mazmanian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a Swedish study found that a majority of self-employed men and a large majority of self-employed women gave 'family/lifestyle' motives for becoming self-employed (Johansson Sevä and Öun, 2015). One of the reasons for this is that self-employment appears to offer possibilities for a 'spatial reconfiguration' of work (Ekinsmyth, 2014;Halford, 2005) and, associated with this, increased temporal flexibility. Thus studies find that women, especially new mothers, look to home-based self-employment to facilitate the management of competing demands (Berke, 2003;Carrigan and Duberley, 2013;Ekinsmyth, 2014;Lewis et al, 2015;Luckman, 2015).…”
Section: Time Space and Self-employmentmentioning
confidence: 99%
“…In many cases, the need for belonging will not come true in virtual spaces (Brown & O´Hara, 2003;Hallford, 2005;Mann & Hodsworth, 2003, Perry et al, 2001. The lack of belonging is affected also by limited access to colleagues and individuals, who are distant.…”
Section: The Elements Of Psychosocial Comfort and Fit In The Virtualmentioning
confidence: 99%
“…Some of the connectivity problems are derived from the limited skills of mobile workers in employing virtual settings and infrastructure (Hallford, 2005;Mann & Holdsworth, 2003;Mark & Su, 2010;Perry & Brodie, 2006;Vartiainen & Hyrkkänen, 2010;Venezia & Allee, 2007). Time constraints and tight schedules of mobile employees together with timeconsuming downloads of connections and programs also make it unreasonable to start virtual work (Axtell et al, 2008;Brown & O'Hara, 2003;Breure & van Meel, 2005;Mark & Su, 2010;Perry et al, 2001;Perry & Brodie, 2006).…”
Section: The Elements Of Functional Comfort and Fit In The Virtual Womentioning
confidence: 99%
See 1 more Smart Citation